Mast Cell Activation and Microtubule Organization Are Modulated by Miltefosine Through Protein Kinase C Inhibition - Rubíková, Zuzana; Sulimenko, Vadym; Paulenda, Tomáš; Dráber, Pavel (Frontiers in Immunology, 2018)
Mast cells play an effector role in innate immunity, allergy, and inflammation. Antigen-mediated activation of mast cells initiates signaling events leading to Ca2+ response and the release of inflammatory and allergic mediators from granules. Diseases associated with deregulated mast cell functions are hard to treat and there is an increasing demand for new therapeutic strategies. Miltefosine (hexadecylphosphocholine) is a new candidate for treatment of mast cell-driven diseases as it inhibits activation of mast cells. It has been proposed that miltefosine acts as a lipid raft modulator through its interference with the structural organization of surface receptors in the cell membrane. However, molecular mechanisms of its action are not fully understood. Here we report that in antigen-activated bone marrow-derived mast cells (BMMCs), miltefosine inhibits degranulation, reorganization of microtubules as well as antigen-induced chemotaxis. While aggregation and tyrosine phosphorylation of IgE receptors were suppressed in activated cells pre-treated with miltefosine, overall tyrosine phosphorylation levels of Lyn and Syk kinases, and Ca2+ influx were not inhibited. In contrast, lipid raft disruptor methyl-β-cyclodextrin attenuated the Ca2+ influx. Tagged-miltefosine rapidly localized into the cell interior, and live-cell imaging of BMMCs with labeled intracellular granules disclosed that miltefosine inhibited movement of some granules. Immunoprecipitation and in vitro kinase assays revealed that miltefosine inhibited Ca2+- and diacylglycerol-regulated conventional protein kinase C isoforms (cPKCs) that are important for mast cell degranulation. Inhibition of cPKCs by specific inhibitor Ly333531 affected activation of BMMCs in the same way as miltefosine. Collectively, our data suggest that miltefosine modulates mast cells both at the plasma membrane and in the cytosol by inhibition of cPKCs. This alters intracellular signaling pathway(s) directed to microtubules, degranulation and migration